Attentional bias to diabetes cues mediates disease management improvements in a pilot randomized controlled trial for adolescents with type 1 diabetes. (December 2021) - Crochiere, Rebecca J; Hughes Lansing, Amy; Carracher, Ann; Vaid, Esha; Stanger, Catherine
For type 1 diabetes management, the role of attentional bias remains unclear. This secondary analysis examined type 1 diabetes attentional bias and adolescent type 1 diabetes management prior to and during a cognitive and behavioral intervention. Youth with type 1 diabetes and above target glycemic control were assigned to intervention or usual care control. Participants completed baseline and follow-up type 1 diabetes Stroop tasks, HbA1c tests, and blood glucose meter downloads. Intervention was associated with greater reductions in type 1 diabetes attentional bias than control, and these reductions partially mediated the effect of treatment on diabetes management behaviors. Type 1 diabetes attentional bias is a potential target to improve type 1 diabetes management.